2017
DOI: 10.3389/fimmu.2016.00688
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothesis of the Human iNKT/Innate CD8(+) T-Cell Axis Applied to Cancer: Evidence for a Deficiency in Chronic Myeloid Leukemia

Abstract: We recently identified a new human subset of NK-like [KIR/NKG2A(+)] CD8(+) T cells with a marked/memory phenotype, high Eomesodermin expression, potent antigen-independent cytotoxic activity, and the capacity to generate IFN-γ rapidly after exposure to pro-inflammatory cytokines. These features support the hypothesis that this new member of the innate T cell family in humans, hereafter referred to as innate CD8(+) T cells, has a role in cancer immune surveillance analogous to invariant natural killer T (iNKT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 38 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…These features validate the KIR/NKG2A(+) Eomes(+) CD8(+) T-cell compartment as a new member of the innate T cell family in humans, and we have termed them innate CD8(+) T cells (41). …”
Section: Human Nk-like Cd8(+) T Cells Express Eomes and Display Innatmentioning
confidence: 56%
See 3 more Smart Citations
“…These features validate the KIR/NKG2A(+) Eomes(+) CD8(+) T-cell compartment as a new member of the innate T cell family in humans, and we have termed them innate CD8(+) T cells (41). …”
Section: Human Nk-like Cd8(+) T Cells Express Eomes and Display Innatmentioning
confidence: 56%
“…Interestingly, our own results (38) have shown a relation of proportionality between PLZF expression in T and iNKT lymphocytes and Eomes expression by innate CD8(+) T cells in cord blood, suggesting that iNKT cells control the differentiation of human innate CD8(+) T cells. Our results in vitro (41) suggest that IL-4 favors Eomes expression and the generation and/or expansion of human innate CD8(+) T cells.…”
Section: The Factors Associated/implicated In Control Of the Differenmentioning
confidence: 65%
See 2 more Smart Citations
“…However, it has been unclear from studies of mice with BCR signaling mutations whether antigen is required or whether purely tonic BCR signals are sufficient for splenic follicular B cell development [12,14,40,41]. Certainly, antigen-driven selection into the innate-like B-1a compartment is well-appreciated, while strong BCR signaling disfavors adoption of marginal zone B cell fate [13,4244]. Prior work has supplied indirect evidence for antigen-dependent positive selection of follicular B cells [12,14,40]; studies have shown that self-ligands can drive selection of B cells into the mature primary immune repertoire [45] and analysis of antigen receptor repertoire diversity has revealed a restricted repertoire in mature relative to immature B cells [4648].…”
Section: Lymphocyte Development and Selection: Setting The Stage For mentioning
confidence: 99%